Pengaruh Perubahan Pembelajaran Daring Ke Luring Terhadap Motivasi Belajar dan Kemampuan Literasi Digital Mata Pelajaran TKR Di SMK Tamansiswa Yogyakarta - Wilibrodus Rahayaan; Suparmin; Alfat Khaharsyah (JURNAL VOKASI DEWANTARA (JVD), 2025)
The purpose of this study was to determine the effect of changing online to offline learning on students' learningmotivation and digital literacy abilities at Tamansiswa Vocational School, Yogyakarta. This research is research usingquantitative methods. The data collection technique used is a questionnaire or questionnaire. The data analysis methoduses descriptive analysis, but before descriptive analysis, prerequisite analysis tests are carried out first. Descriptiveresearch results show that student learning motivation when changing from online to offline learning is 43.4%, witha known R square value of 0.434. Students' digital literacy abilities when changing from online to offline learning are25.5%, with an R square value of 0.255. With these results, the change from online to offline learning increasesstudents' learning motivation and digital literacy skills at Tamansiswa Vocational School, Yogyakarta.